Website user experience model: testing on journalists. (25th August 2022) - Purwadi, Purwadi; Irwansyah, Irwansyah
This research aimed to analyse the components of the website user experience (WUX) and the influence of WUX on brand trust. Another objective was to build a WUX model from the perspective of journalist users. This research approach was quantitative with an online survey method. The research sample was 300 journalists. Partial least square-structural equation modelling (PLS-SEM) was used for data processing techniques and hypothesis testing. This research found two alternative WUX models. The first alternative WUX model showed a significant relationship between WUX (with six components in WUX) to brand trust. The second alternative WUX model showed a meaningful relationship between access speed, user value, user's emotion (three components in the WUX framework that were treated as variables) to brand trust. Of the two models, this research recommended the first alternative WUX model because the components of WUX were better and more complex.